Dividend payouts: Evidence from U.S. bank holding companies in the context of the financial crisis - Abreu, José Filipe; Gulamhussen, Mohamed Azzim (Journal of Corporate Finance, 2013)
We study dividend payouts of 462 U.S. bank holding companies before and during the 2007–09 financial crisis. Fama and French (2001) characteristics (size, profitability and growth opportunities) explain dividend payouts before and during the financial crisis. The agency cost hypothesis explains dividend payouts before and during (more pronouncedly) the financial crisis. The signaling hypothesis explains dividend payouts during the financial crisis. Regulatory pressure was ineffective in limiting dividend payouts by undercapitalized banks before the financial crisis. Our findings have implications for corporate finance and governance theories, and also for the regulatory reforms that are being discussed among policymakers.